1998
DOI: 10.1144/gsl.eng.1998.013.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the wear characteristics of aggregate exposed at the road surface

Abstract: This paper considers the assessment of highway surfacing aggregate wear using the Aggregate Abrasion Value and micro-Deval test methods. Their historical development is discussed. The influence of test sample preparation and number of chippings assessed is compared. Data for both methods are presented for a range of rock types. Dry, wet and soaked versions of the micro-Deval test are compared. The use of a density correction to modify the micro-Deval test value is proposed. The ability of the Aggregate Abrasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The pore fluid seems to influence that stage of damage, with visible differences in the propensity for abrasion in the different RUNs. In dry conditions (RUN 1 and RUN 2) the rolling and sliding between grains generate fines which could have formed a cushion (Woodside & Woodward, 1998;Lin & Lourenço, 2020), damping the impact of the steel balls between particles as shown in Figure 10a. In RUN 3, on the one hand, the viscosity of water reduces the grain dynamics during rotation (Chou et al, 2014), thus the intensity of particle interactions decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The pore fluid seems to influence that stage of damage, with visible differences in the propensity for abrasion in the different RUNs. In dry conditions (RUN 1 and RUN 2) the rolling and sliding between grains generate fines which could have formed a cushion (Woodside & Woodward, 1998;Lin & Lourenço, 2020), damping the impact of the steel balls between particles as shown in Figure 10a. In RUN 3, on the one hand, the viscosity of water reduces the grain dynamics during rotation (Chou et al, 2014), thus the intensity of particle interactions decreases.…”
Section: Discussionmentioning
confidence: 99%
“…They trace the reason for this phenomenon to the fact that friction between aggregate particles decreases when aggregate is saturated. A similar comparison was performed for the M DE/DS test by Strzałkowski [ 83 ] and Woodside and Woodward [ 84 ]. They demonstrated that the abrasion value of saturated aggregates is greater than the abrasion value of dry aggregates.…”
Section: Wear and Fragmentation Resistance Of Mineral Aggregates—a Review Of Micro-deval And Los Angeles Testsmentioning
confidence: 89%
“…Test results show that, there is a rapidly decreasing in skid numbers on the test roads during the winter season. Woodside and Woodward[21] conducted on abrasion test on damp and dry aggregates and reported that damp aggregates exhibit weaker strength. Thus, in the presence of water, aggregates wear more rapidly.…”
mentioning
confidence: 99%